MOBILISASI DAN SUSTAINABILITAS PEMBIAYAAN PEMBERANTASAN MALARIA DI KOTA JAYAPURA - , Dikson B.Womsiwor; , Prof. dr. Laksono Trisnantoro, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The funding of Malaria elimination in The City of Jayapura by APBD/Special Autonomy of 2010 was logging or find other negative expresions, which was less than 10% from 15% of total fund per year in Health section. Thus, this program obtained the assistance by the existing IPM-5 GF Donor (Intensification of Malaria removal â 5 provinces of Indonesia Global Fund). In 2007, the donor aid was temporarily clogged so it caused the case increasing. The implementation of this program requires maximally and continuously funding, so that it turns as top priority of Local Government, related institution and society. The aim of this research is to seek an overview in order to make financing scenario of Malaria elimination program in Health Service of The City of Jayapura as well as to know how far the efforts conducted to improve and maintain the continuity of the program. Research Method: The research is conducted qualitatively by using in depth interview method with the informant of Local Government of The City of Jayapura and related Institution (Health Service) and by document observation and report related with the research. Result of Research: The funding of Malaria program is based on the quality reaching 80%, while, quantity based, the funding has not sufficient (currency 30.000.000 ) or 0,06% per year from 15 % total fund of Special Autonomy or 7,8 billion for health section per year. Indeed, there is a rising each year, but it is below 1%. Thus, based on the agreement with benefactor institution, it should be fifty-fifty, where the fund provided by donor in each year is 300.000.000- 500.000.000, even more. The obstacle happened is the fund provided is huge enough (800.000.000) for PMK section per year, yet it divides into all over disease programs, so that it becomes in small amount and there is no coordination as well as communication inter-department of planning and budgeting (Integration). Conclusion: The Malaria elimination in The City of Jayapura should be a top priority, either the program or the funding from APBD/Special Autonomy as well as other fund sources. For PMK section, the fund is necessarily to be added. The funding is adjusted immediately with the agreement mutually conducted of the donor. It needs coordination and communication inter-department of planning and program manager, eventually the program performance requires increasing and maintaining.